2002
DOI: 10.7863/jum.2002.21.10.1165
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Findings of Acute Urinary Retention Secondary to an Impacted Pelvic Mass

Abstract: Objective. To describe the sonographic findings in a series of cases of acute urinary retention due to an impacted pelvic mass. Methods. The anatomic changes of the lower urinary tract in 6 patients with impacted pelvic masses and acute urinary retention (3 cases of an impacted uterine leiomyoma and 3 cases of a retroverted gravid uterus) were evaluated with transabdominal and transvaginal sonography. Results. When patients were in the supine position, the impacted pelvic masses displaced the cervix superiorly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 5 publications
(8 reference statements)
2
30
2
1
Order By: Relevance
“…A number of case reports/series have documented the relationship between uterine fibroids and voiding dysfunction, including acute urinary retention [5][6][7]. An ultrasound study suggested that the presence of a posterior fibroid might displace the cervix anteriorly, causing compression of the bladder neck and resulting in bladder outlet obstruction and subsequent urinary retention [8]. Less clear is the relationship between urinary frequency and urgency, but presumably pressure on the bladder from the pelvic mass can result in decreased bladder capacity and subsequent urgency and lower voided volumes.…”
Section: Introductionmentioning
confidence: 99%
“…A number of case reports/series have documented the relationship between uterine fibroids and voiding dysfunction, including acute urinary retention [5][6][7]. An ultrasound study suggested that the presence of a posterior fibroid might displace the cervix anteriorly, causing compression of the bladder neck and resulting in bladder outlet obstruction and subsequent urinary retention [8]. Less clear is the relationship between urinary frequency and urgency, but presumably pressure on the bladder from the pelvic mass can result in decreased bladder capacity and subsequent urgency and lower voided volumes.…”
Section: Introductionmentioning
confidence: 99%
“…IV piyelografide eğer intravezikal veya submukozal bir leiomiyom varsa görüntülemede dolma defekti izlenebilmektedir. 13 Çalışmalarda hastaların %87'sinde tanı sistoskopik olarak konmuş ve bimanuel muayenede kitle lastik kıvamında, mobil, düz-gün yüzeyli lezyon olarak palpe edilmiştir. Tanı genellikle üroloji kliniklerinde konulmaktadır.…”
Section: Discussionunclassified
“…It exhibits characteristics similar to those of uterine myomas on US, CT and MRI [3][4][5][6][7][8]. US, CT, MRI, and cystoscopy are valuable diagnostic tools that can depict the morphology and anatomic location of leiomyomas [3][4][5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…It may occur at different ages [3][4][5], can be asymptomatic, or can present in a varied manner, depending on the location of the tumor, with obstructive symptoms, irritating symptoms, hematuria, pelvic mass, and pelvic and flank pain [3][4][5][6][7][8]. Leiomyomas arise in the submucosa, but the growth may be submucosal (7%), intravesical (63%), or extravesical (30%) [5].…”
Section: Discussionmentioning
confidence: 99%